Factors that influence STEM faculty use of evidence-based instructional practices: An ecological model. - Rebecca L Sansom; Desiree M Winters; Bryn E St Clair; Richard E West; Jamie L Jensen (PLoS ONE, 2023)
Traditional teaching practices in undergraduate science, technology, engineering, and mathematics (STEM) courses have failed to support student success, causing many students to leave STEM fields and disproportionately affecting women and students of color. Although much is known about effective STEM teaching practices, many faculty continue to adhere to traditional methods, such as lecture. In this study, we investigated the factors that affect STEM faculty members' instructional decisions about evidence-based instructional practices (EBIPs). We performed a qualitative analysis of semi-structured interviews with faculty members from the Colleges of Physical and Mathematical Sciences, Life Sciences, and Engineering who took part in a professional development program to support the use of EBIPs by STEM faculty at the university. We used an ecological model to guide our investigation and frame the results. Faculty identified a variety of personal, social, and contextual factors that influenced their instructional decision-making. Personal factors included attitudes, beliefs, and self-efficacy. Social factors included the influence of students, colleagues, and administration. Contextual factors included resources, time, and student characteristics. These factors interact with each other in meaningful ways that highlight the hyper-local social contexts that exist within departments and sub-department cultures, the importance of positive feedback from students and colleagues when implementing EBIPs, and the need for support from the administration for faculty who are in the process of changing their teaching.